Anti-inflammatory Effect of Ketamine: A Double-Blind Placebo-Controlled Randomised Study. (September 2021) - Nikkheslat, N; Kotoula, V; Mazibuko, N; Mondelli, V; Mehta, M; Pariante, C.M.
Abstract : Background: Considering the rapid antidepressant action of ketamine, we aimed to investigate its anti-inflammatory effect. Methods: As part of a randomised double-blind placebo-controlled study plasma samples from 31 healthy remitted depressed were collected before and 1.5 hours after ketamine (0.5 mg/kg) and saline (placebo) administration in a two-period cross-over design. Meso Scale Discovery was used to measure cytokines concentrations. Results: Significant interaction effect between the treatment and time were found for IL-1beta (F=8.35, p=0.008), TNF-alpha (F=5.17, p=0.032), IFN-gamma (F=8.78, p=0.006) and GM-CSF (F=5.19, p=0.031). Following ketamine administration, there was a significant decrease in the levels of IFN-gamma (p<0.001) and GM-CSF (p=0.021); but not after placebo infusion (p>0.05). Delta for changes in cytokine concentration in response to ketamine showed statistical significance for IL-1beta, TNF-alpha, and IFN-gamma (p<0.05), and a trend for GM-CSF (p=0.072). Conclusions: Ketamine exhibits anti-inflammatory properties by the effect on the major proinflammatory cytokines including IL-1beta, TNF-alpha, IFN-gamma and GM-CSF. Ketamine could be useful for treatment resistant depression or suicidal thoughts, and our findings suggest that rapid changes in inflammatory markers to be studied as potential mediators of these effects, especially in patients with higher levels of inflammation.